Public school teachers’ perceptions of Educational Psychologists’ services in Limpopo Province (Mamaila circuit) - Macchweu, Makobo Nomsa (My University, 2020)
South Africa, as a member to the global community has ratified global statutes like the Sustainable Development Goals 2030, Education for All, and No Child Left Behind Act. At a national level the progressive democratic policy, the Inclusive Education White Paper 6, supports the mandate to ensure that all children have access to quality education. Lack of learner support and a misfit in the school context are some of the factors that contribute to the low performance and high school dropout rates in Limpopo Province. Therefore, a collaboration between teachers and Educational Psychologists may reduce the effects of the above-mentioned factors. The services of Educational Psychologists are, therefore, pertinent to the provision of psychological, learning and developmental support needs for children, and for teachers. It is against this backdrop that this study provides a snapshot on educational support perceptions of rural teachers and learners in the Mamaila Circuit, in the Limpopo Province of South Africa. The study focuses on teachers’ access to learning support services, with particular reference to the professional services provided by the Educational Psychologists. Eighteen public school teachers were interviewed in two focus groups, in a primary and a secondary school. Findings indicate a gap in teachers’ understanding of the nature of learning support services provided by Educational Psychologists, and the community’s inaccessibility to such services. The results of this study have implications for the Department of Education’s strategies to provide not only access to schooling, but quality education for all children, including rural children.
A research report submitted in fulfilment of the requirement for the degree Master of Education in Social Psychology to the Faculty of Humanities, School of Education, University of the Witwatersrand, Johannesburg, 2020